Bermain Peran Sebagai Metode Psikoedukasi Anak Yatim Duafa Masjid At-Taufiq Guntur Jakarta Selatan dalam Menghadapi Perundungan - Hermeilia Megawati; Herdiyan Maulana; Zarina Akbar; Enno Rahma Putri Sumarto; Salsabila Rifda Permana; Sarahmita Mahsya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Cases of verbal and non-verbal bullying often occur around us, whether we realize it or not. This bullying has a negative impact on victims, so it is important to make efforts to prevent and stop cases of bullying. One way to handle cases of bullying is to provide psychoeducation to children about the negative effects that can arise from cases of bullying. For the reason this research was conducted in the form of psychoeducation for dhuafa orphans under the guidance of the At-Taufiq Guntur Mosque, South Jakarta by using the role-playing method which was carried out face to face. Through formative evaluations and observations made after the activity, it was concluded that the role-playing psychoeducational activities carried out proved successful in achieving the goals that had been designed, namely students gain an understanding of bullying and have skills on how to deal with bullying.